Analisis Fungsi Bahasa Dalam Lirik Lagu Daerah Rejang “Anak Kunang” Karya Idil/Widison - Erna, Erna; Zasrianita, Fera; Wediasti, Welti (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This study aims to analyze the functions of language in the lyrics of the Rejang regional song titled "Anak Kunang" by Idil/Widison, focusing on two perspectives: the language function theory of Chaer and Agustina and Jakobson's theory. The method used is qualitative descriptive analysis, where data are obtained from the song lyrics and then analyzed based on relevant language functions. The research findings reveal that the lyrics contain various language functions, such as personal, directive, phatic, referential, and metalingual functions according to Chaer and Agustina, as well as referential, emotive, conative, metalingual, and phatic functions according to Jakobson. In conclusion, the song "Anak Kunang" serves not only as a source of entertainment but also as a medium rich in meaning that conveys the social and cultural values of the Rejang community. This study emphasizes the importance of language as a communication tool that can strengthen social bonds and reflect cultural identity.